2014
DOI: 10.1038/srep05580
|View full text |Cite
|
Sign up to set email alerts
|

Similar morphological and molecular signatures shared by female and male germline stem cells

Abstract: The existence of mammalian female germline stem cells (FGSCs) indicates that mammalian ovaries possess germline stem cells analogous to testis, and continue to produce gametes postnatally, which provides new insights into female fertility. In this study, we compared the morphological and molecular characteristics between FGSCs and spermatogonial stem cells (SSCs) by analysis of morphology, immunofluorescence, alkaline phosphatase activity assay, reverse transcription polymerase chain reaction (RT-PCR) and micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
49
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 54 publications
5
49
0
Order By: Relevance
“…An anti-DDX4 antibody raised against the C-terminal 25 residues of human DDX4 (here onwards defined as DDX4 C25 antibody) has been used to isolate by MACS or FACS a small population of OSCs from adult ovary in mouse111213141718192025. The C-terminus shares high sequence homology between human and mouse, making this possible (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An anti-DDX4 antibody raised against the C-terminal 25 residues of human DDX4 (here onwards defined as DDX4 C25 antibody) has been used to isolate by MACS or FACS a small population of OSCs from adult ovary in mouse111213141718192025. The C-terminus shares high sequence homology between human and mouse, making this possible (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have not reached a consensus over whether freshly sorted putative OSCs already express these germline markers, with some studies demonstrating expression111214171925 and others not1516.…”
Section: Resultsmentioning
confidence: 99%
“…Oogonial stem cells (OSCs, also termed FGSCs) with oogenic capacity were also successfully isolated and purified from adult mice and healthy reproductive-age women using fluorescence-activated cell sorting (FACS) with the same antibody13. We also showed similar morphological and molecular signatures shared by FGSCs and SSCs14. A growing body of research demonstrated that FGSCs could be achieved from mammalian ovary including mouse, rat, and human11121314151617181920212223242526.…”
mentioning
confidence: 80%
“…Although, compared with SSCs, less is known about FGSCs, an increasing number of research is now being focused on FGSCs [13, 6, 14]; in particular, the isolation and characterization of FGSCs from rat and human ovaries have allowed their biological functions and applications to be studied further [7, 1517]. …”
Section: Introductionmentioning
confidence: 99%